2018
DOI: 10.1017/s1478951518000731
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of interpersonal coping on meaning in spirituality and quality of life and the influences of depression and anxiety thereon in cancer patients

Abstract: ObjectiveThis study aimed to investigate associations among spirituality, coping strategies, quality of life (QOL), and the effects of depression and anxiety thereon in cancer patients.MethodIn total, 237 cancer patients referred to a psycho-oncology clinic at a university hospital in Korea were enrolled. After identifying predictors of patient QOL in a stepwise regression model, we developed a hypothetical path model wherein interpersonal coping was considered as a mediating variable between spirituality (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The results of a study by Moritz et al (22) suggest that spiritual content, including spiritual awareness of self-forgiveness, compassion, appreciation, and daily life Acceptance, reduces depression. In addition, the results of studies by Cha et al ( 23), Rentala et al (24), and Hourani et al ( 25) also indicate the effect of spirituality on patient depression (23)(24)(25), which is consistent with the present study findings. Spirituality is one of the dimensions of human beings that shows the connection and integration of the individual with the universe.…”
Section: Discussionsupporting
confidence: 92%
“…The results of a study by Moritz et al (22) suggest that spiritual content, including spiritual awareness of self-forgiveness, compassion, appreciation, and daily life Acceptance, reduces depression. In addition, the results of studies by Cha et al ( 23), Rentala et al (24), and Hourani et al ( 25) also indicate the effect of spirituality on patient depression (23)(24)(25), which is consistent with the present study findings. Spirituality is one of the dimensions of human beings that shows the connection and integration of the individual with the universe.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, they experienced lower levels of anxiety and depression and had better religious orientation [36]. The results of a study in Korea also found that whenever cancer patients searched for the meaning of a better life, their spiritual well-being and coping skills improved accordingly [37]. Thus, as the search for meaning is important for cancer patients, it needs to be promoted through spirituality-based education.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Spirituality has been shown to be a potential mediator for distress and anxiety. 7,8 Adults with cancer who rated their spiritual beliefs with high importance had less depressive symptoms after treatment compared to those with little or no spiritual beliefs. 9 Less is known about spirituality and spiritual needs in parents who have children diagnosed with cancer and other serious illness.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of cancer care, the spirituality of adults diagnosed with cancer are important components of coping, quality of life, and sense of peace 5,6 . Spirituality has been shown to be a potential mediator for distress and anxiety 7,8 . Adults with cancer who rated their spiritual beliefs with high importance had less depressive symptoms after treatment compared to those with little or no spiritual beliefs 9…”
Section: Introductionmentioning
confidence: 99%